Sovietisation of Schools in the 1940/41 School Year: the Role of Writers in “Re-educating” Teachers; Establishment of the Pioneer Organisation in Schools of Šakiai County; Teachers between Resistance, Conformism and Collaboration; Repressions (4) - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2015)
The article is dedicated to certain aspects of the Sovietisation of general education schools in Lithuania in the 1940/41 school year. It provides the facts of the Bolshevik indoctrination in the local area – Šakiai county schools. The “re-education” of teachers essentially started on 14–15 August 1940, at the Lithuanian Teachers’ Congress held in Kaunas Sports Hall. The matters important for teachers were overshadowed by calls to implement the “socialist spirit” and praises to Josif Stalin and the Red Army. At the end of the Congress, teachers spontaneously protested against the two-day “socialist education” and lies about independent Lithuania in 1918–1940, by signing the Lithuanian national anthem instead of the Internationale. This moral resistance had implications later, during the deportations of June 1941, where teachers accounted for a disproportionately large share of deportees (more than a quarter of elementary school teachers of Šakiai County were repressed).